ANALISIS INSTRUMEN PENILAIAN BERDASARKAN UJI COBA INSTRUMEN TEKS LAPORAN HASIL OBSERVASI DI KELAS X MPLB SMK NEGERI 7 MEDAN - Hasibuan, Mutiara Sany; Masniari Hutagalung, Surya; Adisaputera, Abdurahman (Universitas Islam Sumatera Utara, 2024)
Given the importance of assessment in learning, it is impossible to separate learning from the assessment component. Teachers can quickly measure students' mastery through assessment. In addition, the instructor can use the evaluation results to determine whether students can learn the material effectively or whether they need to be given the opportunity to retake the material until they master it. Of course, instructor assessments must be accompanied by assessment tools, as these are the instruments teachers use to measure student proficiency levels and assess learning strategies.